Growth and competition of Flavobacterium columnare strains in two different nutrient levels - Nkembeng, Aloysius (2016)
Human influence on the environment has led to changes in ecological factors which have greatly contributed to the emergence of different infectious diseases. The introduction of parasites in a new or changed environment can cause mass mortalities in their hosts. However, the reasons for disease outbreaks caused by pathogens are not quite clear, i.e., whether they are caused by changes in epidemiology or evolution of pathogens or both. One factor that can affect the growth of pathogens is nutrient availability. This effect can be different between virulent and avirulent strains due to the influence the available nutrients have on their growth and virulence. Intensive fish farming has created a nutrient rich environment that may favor the growth of pathogens. The objective of this study was to investigate how different nutrient levels will influence the growth of virulent and avirulent strains of Flavobacterium columnare when grown individually as monocultures or together in competition. This study was based on the hypothesis that virulent strain grows better and outcompetes the avirulent strain when nutrient availability is high. However, due to high nutrient requirements it cannot outcompete avirulent strain when nutrient availability is low. It was shown that in both high and low nutrient availability the virulent strain outcompeted the avirulent strain. In competition, it is possible that the virulent strain can grow at lower concentration of limiting nutrient and outcompete the avirulent strain. The results suggest that virulent strains can grow better than avirulent strains both in natural environment where nutrient level is low or in nutrient rich environment, for example at fish farms.